Small but Salient: The Securitization of Ukraine’s Ethnic Hungarian Minority - Balogh Péter; Kovály Katalin; Коваль Катерина (Cambridge University Press, 2024)
Abstract. This article analyzes the key factors behind the securitization of Ukraine’s small ethnic Hungarian minority in recent years and how they affect local interethnic as well as interstate relations. It draws on elite interviews conducted in the Ukrainian-Hungarian borderland, and other sources including speech acts. Four underlying factors were identified. The first two are Hungary’s kin-state aid and dual citizenship law, which have empowered Ukraine’s ethnic Hungarians, with the community appearing larger and potentially more threatening in the eyes of the majority population than its mere size justifies. The other two factors are Ukraine’s language policy and Transcarpathia’s future being subject of conspiracy theories in light of Russia’s invasion of eastern Ukraine, which have negatively affected interethnic ties, although somewhat less in the borderland than between Hungary and Ukraine at large. In Transcarpathia, our different informants had diverging perceptions of who is stirring tensions but agreed that actors from outside their region were to blame. Overall, what has emerged is a clash of Hungary’s kin-state politics and Ukraine’s nation-statebuilding efforts. The article ends with more general implications for kin- and host-state relations in times of conflict.
Editorial board: https://www.cambridge.org/core/journals/nationalities-papers/information/about-this-journal/editorial-board
Content: https://www.cambridge.org/core/journals/nationalities-papers/firstview?pageNum=2&searchWithinIds=C480B8F2C40A05CE0C10D2037E96FA58&productType=JOURNAL_ARTICLE&sort=canonical.date%3Adesc%2CtitleSort%3Aasc&pageSize=20&template=cambridge-core%2Fjournal%2Farticle-listings%2Flistings-wrapper&displayNasaAds=false&hideArticleJournalMetaData=true
https://edit.elte.hu/xmlui/handle/10831/113327
Keywords: minority securitization; kin-state politics; minority salience; group homogeneity; Transcarpathia